Open Reduction and Fixation in Acute Laryngeal Trauma Under Endoscopic Guidance - Jaren R. Cabudol; Joel A. Romualdez; Eutrapio S. Guevara (Philippine Journal of Otolaryngology Head and Neck Surgery, 2019)
Acute laryngeal trauma is a great challenge for the otoloaryngologist. Early recognition, accurate evaluation and proper treatment may be crucial to immediate survival and long-term function.